Improving wear resistance of steels through nanocrystalline structures obtained by bainitic transformation. Issue 4 (3rd March 2016) - Rementeria, R.; Aranda, M. M.; Garcia-Mateo, C.; Caballero, F. G.
Abstract : Nanocrystalline materials are structurally characterised by a large density of grain boundaries which significantly alter their mechanical properties in comparison with conventional coarse-grained materials. Specifically, nanocrystallisation has been proven to be an effective method to improve wear resistance of steels. The recent development of the first bulk nanocrystalline steel, which can be produced on a large scale with large dimensions solely by bainitic transformation at low temperature, has stimulated research in quest of its in-service properties and potential applications. This paper outlines the work devoted in the last years to assess and understand the wear response of those nanocrystalline bainitic steels.